1982
DOI: 10.1104/pp.69.4.921
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Photosynthesis in Agropyron smithii Rydb.

Abstract: ABSTRACTof photosynthesis observed at above-optimum temperatures (3).Temperature has also been shown to affect both the Km (CO2) and V,= of RuBP carboxylase in vitro (2,24). Weis (35) has suggested that a temperature-dependent inactivation of RuBP carboxylase occurs at above-optimal temperatures in intact spinach chloroplasts. Such temperature effects may be partly responsible for the reversible temperature limitations on net photosynthesis observed for intact leaves. However, difficulties arise in interpreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(44 citation statements)
references
References 27 publications
2
41
0
1
Order By: Relevance
“…The conclusions ofthis study are correlated with the conclusions in the accompanying study (12).of the temperature response of whole leaf photosynthesis in A. smithii. In the accompanying study, reversible decreases in the quantum yield of photosynthesis were found to occur between 35 and 42°C.…”
Section: Measurement Of Electronsupporting
confidence: 69%
See 3 more Smart Citations
“…The conclusions ofthis study are correlated with the conclusions in the accompanying study (12).of the temperature response of whole leaf photosynthesis in A. smithii. In the accompanying study, reversible decreases in the quantum yield of photosynthesis were found to occur between 35 and 42°C.…”
Section: Measurement Of Electronsupporting
confidence: 69%
“…In Figure 4, the rate of gram- The temperature range that produces this apparent uncoupling in A. smithii thylakoids (35-40°C) is identical to the temperature range that has been reported to induce uncoupling in spinach thylakoids (13,21). This temperature range is also the range in which C02-saturated photosynthesis in whole leaves of S. smithii becomes limited by temperature (12). Inasmuch as the enzymes of the reductive pentose phosphate pathway have been found to be stable at these temperatures (4), high temperature effects on photophosphorylation may limit photosynthesis in vivo by limiting the regeneration of the substrate for RuBP carboxylase.…”
Section: Measurement Of Electronmentioning
confidence: 64%
See 2 more Smart Citations
“…Whole plant CO2 exchange was measured using an open IR gas analysis system as described previously (8). Ingoing CO2 and 02 concentrations were maintained at 330 Wl/l and 21%, respectively, by mixing gases from cylinders containing 21% 02 in N2, and 1% CO2 in N2 using Wosthoff mixing pumps.…”
Section: Methodsmentioning
confidence: 99%